2014
DOI: 10.1111/jpm.12132
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and psychometric properties of Brøset Violence Checklist in psychiatric care settings in China

Abstract: Short-term risk assessment instrument owns great importance for psychiatric nurses in China; however, the lack of a standardized violence risk assessment instrument has disadvantaged them in clinical practice. The Brøset Violence Checklist (BVC), a behavioural observation tool, is the most frequently cited instrument available for evaluating violence risk in psychiatric inpatients, then worth to be tested in Chinese culture. This study, conducted in two closed wards in a psychiatric hospital in Beijing, reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…Several studies have investigated the psychometric properties of the BVC (Almvik, Woods, & Rasmussen, 2000;Bjorkdahl, Olsson, & Palmstierna, 2005;Hvidhjelm, Sestoft, Skovgaard, & Bue Bjorner, 2014;Yao et al, 2014) and the DASA (Barry-Walsh, Daffern, Duncan, & Ogloff, 2009;Chu et al, 2013;Dumais, Larue, Michaud, & Goulet, 2012;Griffith, Daffern, & Godber, 2013;Vojt, Marshall, & Thomson, 2010). Two cluster randomised controlled trials have demonstrated that the use of the BVC resulted in less aggression and a decreased use of restrictive practices (e.g., seclusion, mechanical restraint and the forced injection of medication) (Abderhalden et al, 2008;van de Sande et al, 2011).…”
Section: Risk Assessment Instrumentsmentioning
confidence: 99%
“…Several studies have investigated the psychometric properties of the BVC (Almvik, Woods, & Rasmussen, 2000;Bjorkdahl, Olsson, & Palmstierna, 2005;Hvidhjelm, Sestoft, Skovgaard, & Bue Bjorner, 2014;Yao et al, 2014) and the DASA (Barry-Walsh, Daffern, Duncan, & Ogloff, 2009;Chu et al, 2013;Dumais, Larue, Michaud, & Goulet, 2012;Griffith, Daffern, & Godber, 2013;Vojt, Marshall, & Thomson, 2010). Two cluster randomised controlled trials have demonstrated that the use of the BVC resulted in less aggression and a decreased use of restrictive practices (e.g., seclusion, mechanical restraint and the forced injection of medication) (Abderhalden et al, 2008;van de Sande et al, 2011).…”
Section: Risk Assessment Instrumentsmentioning
confidence: 99%
“…Inter‐rater reliability for the BVC has been reported in four studies. In the Yao et al () study, the inter‐rater reliability for single item ranged from ICC = 0.41–0.76 with a total ICC = 0.84. Similarly, Almvik et al () reported Kappa values ranging from 0.48 to 1.0 for single item with 100% agreement for the ‘attacking objects’ item, and r = 0.64–1.0 reported by Abderhalden et al ().…”
Section: Resultsmentioning
confidence: 97%
“…This checklist is regarded as a tool that can predict violent behavior, it is fast and easy to use, and it can readily be integrated with day‐to‐day clinical applications to supplement clinical evaluations . The BVC is widely used in a variety of settings worldwide, for example, Norway, Sweden, Switzerland, Canada, Denmark, Portuguese, and China …”
Section: Introductionmentioning
confidence: 99%
“…5,11 The BVC is widely used in a variety of settings worldwide, for example, Norway, 11 Sweden, 18 Switzerland, 16 Canada, 5,22 Denmark, 2 Portuguese, 12 and China. 23 The determination of risks, such as the risk of suicide, risk of falling, and risk of violence, as well as taking necessary measures, is necessary for the psychiatric clinics to ensure the safety of workers and patients. As in all countries, violent behavior in psychiatric inpatients in Turkey can be common.…”
mentioning
confidence: 99%
See 1 more Smart Citation